Chapter The Group as an Education Resource in Guidance Processes - Priore, Alessandra (Studies on Adult Learning and Education, 2018)
The aim of this paper is to see what happens when reflective practice is used in a guidance intervention made with a group. Fifty university students took part in 3 focus group sessions during which they could discuss the issue of guidance and the choices and construction of a life plan. The results show a clear perception of wellness and usefulness in the educational experience, based on the possibility of knowing oneself, comparing oneself with others, activating systematic reflection on oneself and promoting change